The Influence of Innovative Work Behavior and Job Satisfaction on Employee Performance - Loi, Saprantinus (Lentera Ilmu Nusantara, 2024)
This research aims to find out how much influence innovative work behavior and job satisfaction have on the performance of employees of the Jakarta I Health Polytechnic. The method used is a quantitative survey research method carried out by distributing questionnaires which include statements regarding the issues of innovative work behavior, job satisfaction, and employee performance. The population of this study were employees who worked at the Jakarta I Health Polytechnic and took a sample of 55 people. The results of this research found that innovative work behavior does not have a significant effect on employee performance and job satisfaction has a positive effect on employee performance.